Brushing up your listening skills checklist - Nadja Maria Santos Soares; Simone Silveira Amorim (Universidade Federal de Sergipe, 2016)
This article aims at sharing some ideas concerning listening strategies focusing on reducing the burden listening comprehension may cause. It is a project developed with pre-intermediate students and its primary goal was to engage learners into mastering listening strategies by combining as many sub-skills as possible in order to succeed. By delving into authors like Beare; Celce-Murcia; Ur; White; among others we have created a listening checklist to raise their perceptions towards what they had to pay attention to in order to make the best of the listening and as a result, successfully process spoken language and improve their communicative competence.